2009
DOI: 10.1590/s0100-879x2009000600006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the conditioned medium of mesenchymal stem cells on mouse oocyte activation and development

Abstract: Mesenchymal stem cells (MSCs) have been reported to secrete a variety of cytokines and growth factors acting as trophic suppliers, but little is known regarding the effects of conditioned medium (CM) of MSCs isolated from femurs and tibias of mouse on the artificial activation of mouse oocytes and on the developmental competence of the parthenotes. In the current study, we investigated the effect of CM on the events of mouse oocyte activation, namely oscillations of cytosolic calcium concentration ([Ca 2+ ] i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In this regard, Feng et al 22 showed that MSC-CM can efficiently stimulate mouse oocyte by the generation of Ca 2+ oscillations and finalization of meiosis. In this regard, Feng et al 22 showed that MSC-CM can efficiently stimulate mouse oocyte by the generation of Ca 2+ oscillations and finalization of meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, Feng et al 22 showed that MSC-CM can efficiently stimulate mouse oocyte by the generation of Ca 2+ oscillations and finalization of meiosis. In this regard, Feng et al 22 showed that MSC-CM can efficiently stimulate mouse oocyte by the generation of Ca 2+ oscillations and finalization of meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,17 Information regarding the appropriate conditions for human IVM is still minimal. 22,23 EGF and IGF-1 are thought to play important roles in the improvement of meiotic maturation, directly or via CCs. 14 Culture conditions are thought to be the most essential factor affecting IVM efficacy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secretome components secreted by MSCs, such as chemokines, cytokines, and growth factors, are crucial to maintain the homeostasis and signal transduction with stromal cells (fibroblast, endothel cell, macrophage) [37]. These soluble factors in CM determine the fate of stem cells in in-vitro assays [38].…”
Section: Effect Of CM From Co-cultured Hwjmscs and Il-2 Nk Cells Towamentioning
confidence: 99%
“…MSCs secrete secretome such as chemokins, cytokines, growth factor as bioactive and nutrition 50 , these secretome are important to preserve the homeostasis, cross talk with stromal cells (fibroblast, endothel cell, macrophage). The soluble factor of CM affect stem cells fate by in vitro assay.…”
Section: Effect CM From Co-culture Of Hwjmscs and Ils-nk Towards Apopmentioning
confidence: 99%